Patterns of Peripheral Joint Involvement in Psoriatic Arthritis - Symmetric, Ray and/or Row? - Chandran, Vinod (Semin Arthritis Rheum, 2020)
OBJECTIVE: We sought to examine whether joint involvement in psoriatic arthritis (PsA) follows a symmetric, ray, and/or row pattern using longitudinal data. METHODS: Data on activity and clinical damage of the joints of the hands and feet were obtained from a PsA cohort. For each analysis (symmetry, ray or row) for each outcome (joint damage and activity) expected values for table cells under the null hypothesis that joints progress independently to damage or activity were calculated based on a logistic regression model with patient level random effects for the probability of involvement developing between clinic visits. To determine the consistency of observed with expected values, goodness-of-fit tests were performed. RESULTS: Data from 704 patients were available. The 511 (552) patients with no hand (foot) damage at clinic entry were used for analyses of hand (foot) damage. When considering joint damage, there was strong evidence against independence of joint involvement based on evident symmetric patterns. There was little suggestion of ray patterns of joint damage. There was considerable evidence for row pattern of involvement of joints. When considering joint activity, symmetric patterns were also evident but, unlike joint damage, there was evidence of ray patterns, most notably in the hands. There was also evidence for row pattern involvement. CONCLUSION: Patterns of peripheral joint involvement seen over time in PsA patients, demonstrate consistency with expected ray patterns of disease activity, especially in the hands, but there is also considerable evidence for symmetric and row patterns for both joint damage and activity.